Sequential introduction of single room isolation and hand hygiene campaign in the control of methicillin-resistant Staphylococcus aureus in intensive care unit - Cheng Vincent CC; Tai Josepha WM; Chan WM; Lau Eric HY; Chan Jasper FW; To Kelvin KW; Li Iris WS; Ho PL; Yuen KY (BMC Infectious Diseases, 2010)
Abstract Background After renovation of the adult intensive care unit (ICU) with installation of ten single rooms, an enhanced infection control program was conducted to control the spread of methicillin-resistant Staphylococcus aureus (MRSA) in our hospital. Methods Since the ICU renovation, all patients colonized or infected with MRSA were nursed in single rooms with contact precautions. The incidence of MRSA infection in the ICU was monitored during 3 different phases: the baseline period (phase 1); after ICU renovation (phase 2) and after implementation of a hand hygiene campaign with alcohol-based hand rub (phase 3). Patients infected with extended spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella species were chosen as controls because they were managed in open cubicles with standard precautions. Results Without a major change in bed occupancy rate, nursing workforce, or the protocol of environmental cleansing throughout the study period, a stepwise reduction in ICU onset nonbacteraemic MRSA infection was observed: from 3.54 (phase 1) to 2.26 (phase 2, p = 0.042) and 1.02 (phase 3, p = 0.006) per 1000-patient-days. ICU onset bacteraemic MRSA infection was significantly reduced from 1.94 (phase 1) to 0.9 (phase 2, p = 0.005) and 0.28 (phase 3, p = 0.021) per 1000-patient-days. Infection due to ESBL-producing organisms did not show a corresponding reduction. The usage density of broad-spectrum antibiotics and fluoroquinolones increased from phase 1 to 3. However a significant trend improvement of ICU onset MRSA infection by segmented regression analysis can only be demonstrated when comparison was made before and after the severe acute respiratory syndrome (SARS) epidemic. This suggests that the deaths of fellow healthcare workers from an occupational acquired infection had an overwhelming effect on their compliance with infection control measures. Conclusion Provision of single room isolation facilities and promotion of hand hygiene practice are important. However compliance with infection control measures relies largely on a personal commitment, which may increase when personal safety is threatened.